Conservação e restauro das obras do pintor Adriano de Sousa Lopes da Colecção de Pintura da FBAUL - Cardeira, Liliana, 1989- (2018)
In this study we sought to highlight Adriano de Sousa Lopes as a student of the School of Fine Arts of Lisbon and as a scholarship abroad. Here, we present the works belonging to the FBAUL Painting Reserve, made by Sousa Lopes, unprecedented event since the reserve is a recent painting store and some works were indentified ao such during the research for this dissertation. When investigating the works of painting in the time that Adriano de Sousa Lopes was a student at the Academy, they were subjected to various techniques and laboratory exams, including field exams and point exams to investigate every single detail about their implementation and technical, materiality, evaluation of conservation status, etc.. In accordance of historical research, the study was complemented with a practical component, proceeding to the Conservation and Restoration of five paintings of the artist - Batalha entre Gregos e Troianos, Madalena junto ao Túmulo de Jesus, Nu Académico Deitado, Retrato de Senhora com Xaile Vermelho e A Vaca. These five works were selected according to their importance and according priority criteria of preservation by the super Professor Fernando António Baptista Pereira, co-super for the Conservator Maria José Francisco and the researcher responsible for the Painting Reserve, Dr. Luis Lyster Franco. Re-establishe chemical and physical unit of works, restoring their original characteristics, so that they come to life again in an exhibition designed to be presented at the Faculty of Fine Arts, University of Lisbon, on the occasion of the Centennial Celebration of the First World War, in which the artist has participated as an officer of the Portuguese Expeditionary Corps